The Synthesis and Antibacterial Properties of Pillar[5]arene with Streptocide Fragments - Evgenia Subakaeva; Pavel Zelenikhin; Evgenia Sokolova; Arina Pergat; Yulia Aleksandrova; Dmitriy Shurpik; Ivan Stoikov (MDPI AG, 2023)
The growing problem of bacterial resistance to antimicrobials actualizes the development of new approaches to solve this challenge. Supramolecular chemistry tools can overcome the limited bacterial resistance and side effects of classical sulfonamides that hinder their use in therapy. Here, we synthesized a number of pillar[5]arenes functionalized with different substituents, determined their ability to self-association using DLS, and characterized antimicrobial properties against S. typhimurium, K. pneumoniae, P. aeruginosa, S. epidermidis, S. aureus via a resazurin test. Biofilm prevention concentration was calculated for an agent with established antimicrobial activity by the crystal-violet staining method. We evaluated the mutagenicity of the macrocycle using the Ames test and its ability to affect the viability of A549 and LEK cells in the MTT-test. It was shown that macrocycle functionalized with sulfonamide residues exhibited antimicrobial activity an order higher than pure streptocide and also revealed the ability to prevent biofilm formation of S. aureus and P. aeruginosa. The compound did not show mutagenic activity and exhibited low toxicity to eukaryotic cells. The obtained results allow considering modification of the macrocyclic platforms with classic antimicrobials as an opportunity to give them a "second life" and return to practice with improved properties.